Veteran suicide prevention learning collaborative: implementation strategy and processes - Mignogna, Joseph; Russell, Patricia D.; Borah, Elisa; Bryan, Craig J.; Monteith, Lindsey L.; Bongiovanni, Kathryn; Villareal, Edgar; Hoffmire, Claire A.; Peterson, Alan L.; Heise, Jenna; Mohatt, Nathaniel; Baack, Sylvia; et al. (Frontiers in Psychiatry, 2024)
The majority of Veterans who died by suicide in 2021 had not recently used Veterans Health Administration (VA) services. A public health approach to Veteran suicide prevention has been prioritized as part of the VA National Strategy for Preventing Veteran Suicide. Aligned with this approach, VA’s Patient Safety Center of Inquiry—Suicide Prevention Collaborative piloted a Veteran suicide prevention learning collaborative with both clinical and non-clinical community agencies that serve Veterans. The VA COmmunity LeArning CollaboraTive (CO-ACT) uses a quality improvement framework and facilitative process to support community organizational implementation of evidence-based and best practice suicide prevention strategies to achieve this goal. This paper details the structure of CO-ACT and processes by which it is implemented. This includes the CO-ACT toolkit, an organizational self-assessment, a summary of recommendations, creation of a blueprint for change, selection of suicide prevention program components, and an action plan to guide organizations in implementing suicide prevention practices. CO-ACT pilot outcomes are reported in a previous publication.